2022
DOI: 10.3390/ph15070842
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Edaravone on TDP-43 Plus Oxidative Stress-Induced Neurotoxicity in Neuronal Cells: Analysis of Its Neuroprotective Mechanisms Using RNA Sequencing

Abstract: Edaravone is a free-radical scavenger drug that was recently approved for the treatment of amyotrophic lateral sclerosis (ALS), a neurodegenerative disease. A pathological hallmark of ALS is the accumulation of ubiquitinated or phosphorylated aggregates of the 43-kDa transactive response DNA binding protein (TDP-43) within the cytoplasm of motor neurons. This study revealed the efficacy of edaravone in preventing neuronal cell death in a TDP-43 proteinopathy model and analyzed the molecular changes associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…While we investigated the activity of SBT-272 to promote and enhance axonal outgrowth of diseased CSMN, we chose to evaluate two additional compounds known to act on cellular stress and have been investigated in preclinical models of ALS and in patients. These compounds are edaravone, FDA approved for ALS (Brooks et al, 2022; Genge et al, 2022; Ito et al, 2008; Soejima-Kusunoki et al, 2022; Writing and Edaravone, 2017; Yoshino and Kimura, 2006), and AMX0035, an investigational compound approved for the treatment of ALS in Canada (Heo, 2022). Edaravone is believed to be a scavenger of free radical such as 3-nitrotyrosine that cause cellular stress (Ikeda and Iwasaki, 2015; Yoshida et al, 2008; Yoshino and Kimura, 2006) and AMX0035 is reported to be effective in improving the health and stability of mitochondria and endoplasmic reticulum (Paganoni and Cudkowicz, 2020; Paganoni et al, 2022a; Paganoni et al, 2020; Paganoni et al, 2022b).…”
Section: Resultsmentioning
confidence: 99%
“…While we investigated the activity of SBT-272 to promote and enhance axonal outgrowth of diseased CSMN, we chose to evaluate two additional compounds known to act on cellular stress and have been investigated in preclinical models of ALS and in patients. These compounds are edaravone, FDA approved for ALS (Brooks et al, 2022; Genge et al, 2022; Ito et al, 2008; Soejima-Kusunoki et al, 2022; Writing and Edaravone, 2017; Yoshino and Kimura, 2006), and AMX0035, an investigational compound approved for the treatment of ALS in Canada (Heo, 2022). Edaravone is believed to be a scavenger of free radical such as 3-nitrotyrosine that cause cellular stress (Ikeda and Iwasaki, 2015; Yoshida et al, 2008; Yoshino and Kimura, 2006) and AMX0035 is reported to be effective in improving the health and stability of mitochondria and endoplasmic reticulum (Paganoni and Cudkowicz, 2020; Paganoni et al, 2022a; Paganoni et al, 2020; Paganoni et al, 2022b).…”
Section: Resultsmentioning
confidence: 99%
“…While Riluzole does not modify the course of the disease (Fang et al, 2018), it prolongs the patient's survival from 6 to 19 months (Andrews et al, 2020). Edaravone is a potent anti-oxidant and a free-radical scavenger, preventing oxidative stress-induced motor neuron death (Jami et al, 2015;Soejima-Kusunoki et al, 2022). A randomized controlled trial conducted in Japan demonstrated the effectiveness of Edaravone in slowing the rate of motor function deterioration, particularly in selected patients with early disease onset and rapid progression (Writing Group and Edaravone MCI-186 ALS 19 Study Group, 2017).…”
Section: Therapeutic Targeting Of Misfolding and Aggregationmentioning
confidence: 99%
“…At the moment, there are only three drugs available for the treatment of disease symptoms. Riluzole, an inhibitor of glutamate release at synapses [ 12 ], edaravone, a free-radical scavenger and antioxidant [ 13 ], and the latest, relyvrio, a combination of two existing drugs, phenylbutyrate and taurursodiol, that are suggested to hinder mitochondrial and endoplasmic reticulum (ER) stress [ 14 ]. These drugs’ modes of action tackle important disease mechanisms in ALS.…”
Section: Introductionmentioning
confidence: 99%